Identification of regional industrial priority pollutants in surface water: A field study in Taihu Lake Basin - Kang, Ying; Chen, Yuqi; Zhou, Mengjiao; Xu, Yingfeng; Feng, Huajun; Chen, Ruya (Frontiers in Environmental Science, 2022)
The current water environment management of China has gradually shifted from reaching water quality standards to preserving water ecological health, and the control focus has extended from traditional nitrogen and phosphorus pollutants to micropollutants, such as heavy metals and emerging pollutants. However, the precise traceability and regulatory system of micropollutants in different regions’ watersheds was not yet mature. A five-step strategy of risk assessment and management was proposed this study to successfully construct a list of industrial priority pollutants and a list of 376 priority control discharge enterprises in 13 administrative regions of China’s Taihu Lake Basin. Firstly, a preliminary list of 78 pollutants was determined with reference to the emission standards of major regional industrial pollution sources, relevant national environmental regulations and literature reports. Secondly, 22 types of priority control pollutants were re-screened based on the analytical results of surface water samples obtained from 26 monitoring sites in the study area. Then the environmental risk values of the re-screened pollutants were calculated referring to the Chemical Hazard Evaluation for Management Strategy (CHEMS-1) method. Next, the regional environmental risk baseline value was determined and the risk value equivalent (EY) for each pollutant was calculated. Finally, according to the EY results, the regional priority control pollutants were identified, and the priority control discharge enterprises were confirmed retroactively. The results of this study can provide methodological support and a scientific basis for the precise control of micropollutants in surface water from differentiated regions.